Soil respiration dynamics in fire affected semi-arid ecosystems: Effects of vegetation type and environmental factors - Muñoz-Rojas, M.; Lewandrowski, W.; Erickson, T.; Dixon, Kingsley; Merritt, D. (Elsevier, 2015)
© 2016 Elsevier B.V. Soil respiration (Rs) is the second largest carbon flux in terrestrial ecosystems and therefore plays a crucial role in global carbon (C) cycling. This biogeochemical process is closely related to ecosystem productivity and soil fertility and is considered as a key indicator of soil health and quality reflecting the level of microbial activity. Wildfires can have a significant effect on Rs rates and the magnitude of the impacts will depend on environmental factors such as climate and vegetation, fire severity and meteorological conditions post-fire. In this research, we aimed to assess the impacts of a wildfire on the soil CO2 fluxes and soil respiration in a semi-arid ecosystem of Western Australia, and to understand the main edaphic and environmental drivers controlling these fluxes for different vegetation types. Our results demonstrated increased rates of Rs in the burnt areas compared to the unburnt control sites, although these differences were highly dependent on the type of vegetation cover and time since fire. The sensitivity of Rs to temperature (Q10) was also larger in the burnt site compared to the control. Both Rs and soil organic C were consistently higher under Eucalyptus trees, followed by Acacia shrubs. Triodia grasses had the lowest Rs rates and C contents, which were similar to those found under bare soil patches. Regardless of the site condition (unburnt or burnt), Rs was triggered during periods of higher temperatures and water availability and environmental factors (temperature and moisture) could explain a large fraction of Rs variability, improving the relationship of moisture or temperature as single factors with Rs. This study demonstrates the importance of assessing CO2 fluxes considering both abiotic factors and vegetation types after disturbances such as fire which is particularly important in heterogeneous semi-arid areas with patchy vegetation distribution where CO2 fluxes can be largely underestimated.